INVENTARISASI CACING PARASITIK SALURAN PENCERNAAN PADA ELANG JAWA (Spizaetus bartelsi Stressman, 1924) dan ELANG BRONTOK (Spizaetus cirrhatus Gmelin, 1788) DI HABITAT EKS-SITU - Muhamad Cahadiyat Kurniawan; Erna Suzanna; Elok Budi Retnani (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
At present there is a few of javan hawk eagle and changeable hawk eagle on ex-situ habitat Its existence can not avoid from the attack of various diseases, intestinal worm infections is a parasitic disease that can adversely affect and evencause death to these animals. The disease is usulally caused by medical management is inadequate cages. Research was conducted to learn the types of gastrointestinal javan hawk eagle and changeable hawk eagle and the degree of infection. Besides, as an initial study of behavioral factors and health management in eagle at the rehabilitation that may affect the transmition of parasitic worms. Types of parasitic worms found in the javan hawk eagle is Ascaridia sp, Strigea sp, and Capillaria sp. Changeable hawk eagle on the Strigea sp, Neodiplostomum sp, Heterakis sp, Ascaridia sp and Capillaria sp. Obtained two types of worms eggs are Ascaridia sp and Capillaria sp that can bedetected value of TTGT. From Cikananga Wildlife Center namely on changeable hawk eagle 4 there are three eggs Ascaridia sp TTGT value 147,5, while from Gadog Wildlife Center namely javan hawk eagle obtained 19 Capillaria sp with value TTGT 1868. Factors though to the influence the transmission of parasitic worms that is visible behaviour with the claw part of clean beak with the claw, clean the body in the chest and wings by using beak (probe), and placement of the cage that is not appropriate. Keywords: javan hawk eagle, changeable hawk eagle, parasitic worms, TTGT.